Pros and Cons of Early and Very Early Surgery for Traumatic Central Cord Syndrome with Spinal Stenosis: Literature Review and Case Report - Hildebrandt, Gerhard; Joswig, Holger; Stienen, Martin Nikolaus; Bratelj, Denis (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background The case of a 69-year-old patient with an acute traumatic central cord syndrome (ATCCS) with preexisting spinal stenosis raised a discussion over the question of conservative versus surgical treatment in the acute setting. We provide a literature overview on the management (conservative vs. surgical treatment) of ATCCS with preexisting spinal stenosis.Methods We reviewed the literature concerning essential concepts for the management of ATCCS with spinal stenosis and cervical spinal cord injury. The data retrieved from these studies were applied to the potential management of an illustrative case report.Results Not rarely has ATCCS an unpredictable neurologic course because of its dynamic character with secondary injury mechanisms within the cervical spinal cord in the early phase, the possibility of functional deterioration, and the appearance of a neuropathic pain syndrome during late follow-up. The result of the literature review favors early surgical treatment in ATCCS patients with preexisting cervical stenosis.Conclusion Reluctance toward aggressive and timely surgical treatment of ATCCS should at least be questioned in patients with preexisting spinal stenosis.
Keywords: AMS; ASIA; central cord syndrome; cervical trauma; spinal cord injury